Teaching young adult literature today : insights, considerations, and perspectives for the classroom teacher - Hayn, Judith A., 1944-; Kaplan, Jeffrey S., 1951- (Lanham : Rowman & Littlefield Publishers, Inc., 2012)
"Teaching Young Adult Literature introduces the reader to what is current and relevant in the plethora of good books available for adolescents. This smart collection by literary experts illustrates how teachers can help their students become lifelong readers by simply introducing them to smart, insightful, and engaging books"--Provided by publisher.
Introduction -- section 1. Where has YAL been? Young adult literature: defining the role of research / Judith A. Hayn and Amanda L. Nolen -- The changing face of young adult literature: what teachers and researchers need to know to enhance their practice and inquiry / Jeffrey S. Kaplan -- Literacy teacher education today and the teaching of adolescent literature: perspectives on research and practice / Susan E. Elliott-Johns -- section 2: Where is YAL now? Identifying obstacles and garnering support: young adult literature in the English language arts classroom / Kelly Byrne Bull -- Using young adult literature to motivate and engage the disengaged / Michelle J. Kelley, Nance S. Wilson, and Melanie D. Koss -- Dystopian novels: what imagined futures tell young readers about the present and future / Crag Hill -- Out of the closet and into the open: LGBTQ young adult literature in the language arts classroom / Laura A. Renzi, Mark Letcher, and Kristen Miraglia -- Multicultural adolescent literature: finding the balance / Judith A. Hayn and Sarah M. Burns -- Updating young adult literature reading lists while retaining quality titles / Lisa A. Hazlett -- Crossing boundaries: genre-blurring in books for young adults / Barbara A. Ward, Terrell a Young, and Deanna Day -- The best-selling adult novelist and young adult fiction / Steven T. Bickmore -- Young adult literature as a call to social activism / Lois T. Stover and Jacqueline Bach -- section 3. Where is YAL going? Beyond the language arts classroom: the dynamic intersection of young adult literature and technological, pedagogical, and content knowledge / Colleen T. Sheehy and Karina R. Clemmons -- Reading with blurred boundaries; the influence of digital and visual culture on young adult novels / Linda T. Parsons and Melanie Hundley -- YAL in cyberspace: how teachers are following their students into new literacies / James Blasingame -- Index.
Includes bibliographical references and index.
Keywords: Young adult literature -- Study and teaching; Teenagers -- Books and reading -- United States